POLITENESS STRATEGY IN REFUSAL OF THE GUESTS OF THE ELLEN SHOW - Apriyani Rovita; Ingatan Gulo (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2022)
This paper is part of research about politeness strategy in refusal done by guests on The Ellen Show. This study aimed to find out the types of politeness strategies used in the refusal and the ways the strategies are used by the guests in refusing invitations, offers, and suggestions on the talk show. The qualitative method and library research were applied in gathering the data. The researchers collected transcribed conversations of the guests from eleven most viewed videos of The Ellen Show, read them, and analyzed the politeness strategy found in the collected data. As result, the guests used ten politeness strategies in refusal such as solidarity, excuse, promise, showing sympathy and consideration first, explicit and direct expression, expression in a less coercive way, giving hints, being ambiguous, transferring to another topic, and using body language. Positive politeness was used by the guests in refusing the invitation for agreement, gift offer, and unsolicited suggestions; show concern and develop conversation rapport. Negative politeness/bald on record was used in refusing the invitation for acceptance, favor offer, and unsolicited suggestion; show concern. And off record strategies were used in refusing invitation for action, gift offer, favor offer, opportunity offer, solicited suggestion, and unsolicited suggestion; develop conversation rapport. Therefore, the most strategy used by the guests in doing refusal is off record strategies.Keywords: Ellen Show, guests, politeness strategy, refusal